Peran Agama dalam Aktivitas Pelestarian Alam: Studi Deskriptif pada Front Nahdliyyin untuk Kedaulatan Sumber Daya Alam, FNKSDA - Dede Setiawan (Jurnal Penelitian Ilmu Ushuluddin, 2022)
The purpose of this study was to discuss the role of religion in nature conservation activities carried out by the Nahdliyyin Front for Natural Resources Sovereignty. This research is a qualitative research with descriptive method through theoritical analysis and literature study. The results of this study indicate that nature conservation activities the Nahdliyyin Front for Natural Resources Sovereignty has a role for religion. Namely in the form of a power boost called Religious Assets. The religious assets include; 1) Transcendent Motivation; 2) Shared Identity; 3) Socio-Geographical Religion; 4) Special Legitimacy; and 5) Institutional Interests. This research has significance for the development of the discourse of Religious Studies in the field of Religion and Ecology. Considering that the discourse on the relationship between religion and the issue of nature conservation is still considered minimally studied. The conclusion of this study is that religion has a role in the form of encouragement of strength through moral and institutional messages in an effort to preserve nature.